Storyboardgraphy. Issue 4 (20th October 2021) - Angelone, Samer
Abstract : Throughout the history of filmmaking, storyboarding has been used to pre-visualise films and help with production. Here I propose a new film visualisation tool to complement storyboarding, which I call 'Storyboardgraphy' and define as a 'film pre- and post-visualization tool showing shot sizes and lengths along a timeline'. A storyboardgraphic consists of two axes, with the X-axis representing the scene timeline, the Y-axis the size of the shots, and the characters depicted as recognisable curves. Storyboardgraphy is an excellent way of visualising a) shot sizes/lengths in a simple graphic; b) shot pacing (changes in the lengths of shots over the film timeline); and c) the dynamic of shot sizes (the order of shots along the scene timeline), which are not easily perceived on a conventional storyboard. Therefore storyboardgraphy is of huge interest, not only for pre-visualisation and production, but also for post-visualisation when editing, teaching film-making and studying film.